FAKTOR DOMINAN YANG MEMPENGARUHI PENEMPATAN PEGAWAI NEGERI SIPIL DI SEKRETARIAT DAERAH KABUPATEN KUBU RAYA - Megawati E.21109093, Dayang (FISIP Universitas Tanjungpura, 2013)
This thesis is intended to provide an understanding of the factors that affect staffing in the Secretariat long Kubu Raya District , covering education , job knowledge , job skills and work experience . Problems in staffing in Kubu Raya District Secretariat is long in-service staffing is still not based on competence . Besides staffing system is not oriented to the Merit System , such as the classification of positions , job descriptions , competency standards and objective appraisal is still not available . As a result, the placement can not be based on a rational plan needs . From the findings of the research that the factors that influence the placement of employees in this case education , knowledge , skills and work experience has not shown adequate results . So that employees are placed in Kubu Raya District Secretariat work optimally . Keywords : civil servants Placement, Work Experience, Education and Traning of civil servants.